The role of visual communication in improving images of Malaysian secondary school textbooks / N. Yusof and G. Daimin - Yusof, N.; Daimin, G. (2016)
This research will investigate the role of visual communication in enhancing the image of secondary school textbooks in Malaysia. This research presents the issues and problems such elements of visual communication on the textbooks. The study was also revealing comparative visual communication elements between Malaysian textbooks and abroad textbooks. Next, this study was present recommendations for improvement as further efforts to overcome these issues. The research methodology was applied a quantitative approach which is administered by survey instruments to answers the research problem. This study were participated by secondary school students, academician who are teachers and industries expertise who are graphic designer. The study was involved in Shah Alam area. All the data collection were gathered, tabulated and analyzed by using Microsoft Excel. The finding showed, the role of visual communication in enhancing the images of textbook seen needed to transformation and improvement to become more systematic to fulfill the standard quality requirement. To that end, this study was introduced the new identity of visual communication design of KBSM textbook.